A survey of clean air policy in Europe - Helmut Weidner (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1989)
The paper presents a brief overview on the most important developments in European clean air policy. Special consideration is given to the activities in the European Community using, among other things, the results of an international conference on clean air policies in large European cities. In conclusion, some suggestions for improving clean air policy are made. A comprehensive annex of tables provides the reader with current key data on the most relevant aspects of clean air policy in the 12 EC member countries. (This report is an enlarged and revised version of a paper presented at a seminar organized by friends of the Earth and Goethe Institute London on 8/9 December 1987, on The Future for Forests - Science and Policy Issues Surrounding Forest Decline in Europe.) – – Es wird ein kurzer Uberblick zu den wichtigsten Entwicklungen in der europaischen Luftreinhaltepolitik gegeben. Der Schwerpunkt liegt dabei auf den MaBnahmen in der Europaischen Gemeinschaft; hierbei wird unter anderem auf Ergebnisse einer internationalen Konferenz zur Luftreinhaltepolitik in europaischen GroBstadten zurückgegriffen. AbschlieBend werden einige Vorschlage zur Verbesserung der Luftreinhaltepolitik gemacht. Ein umfassender Tabellenanhang gibt aktuelle Informationen zu relevanten Bereichen der Luftreinhaltepolitik in den zwblf EG-Mitgliedslandern.
Keywords: 320